Childhood Abuse, Nonsuicidal Self‐Injury, and Suicide Attempts: An Exploration of Gender Differences in Incarcerated Adults. Issue 6 (13th June 2016) - Power, Jenelle; Gobeil, Renee; Beaudette, Janelle N.; Ritchie, Mary B.; Brown, Shelley L.; Smith, Hayden P.
Abstract : The relationship between types of childhood abuse, suicide attempts, and nonsuicidal self‐injury (NSSI) was examined in a sample of 415 incarcerated adults (268 men, 147 women). Men and women were equally likely to experience childhood abuse, although women were more likely to report sexual abuse and men were more likely to report emotional neglect. Sexual abuse was the only type of abuse found to predict NSSI and suicide attempts in women. For men, physical abuse and physical neglect were significant predictors of NSSI and suicide attempts, respectively. Gender differences exist and should be examined in future research in this area.